Evaluation of the reproductive aptitude of crossbred bulls in the dry tropics in extensive exploitation as a predictor of the bull / cow ratio - Macías Moreira, Yandri Andrés (2022)
The objective of the study was to evaluate the reproductive condition of mestizo bulls in the dry tropics under extensive exploitation conditions, analyzing semen quality and other reproductive characteristics associated with fertility. The research was carried out in the months of September to October 2018, in the Rocafuerte canton, located in the dry tropical zone of the Manabí province, Ecuador. The scrotal circumference and sperm quality of 60 crossbred bulls of different breeds and ages were evaluated under natural mating conditions and without sexual rest before the examination. Semen samples were obtained by electro-ejaculation, with minimal impact on bull welfare. The mean scrotal circumference was 33.1 cm, with a range of 28 to 39.5 cm. It was found that 75% of the bulls are suitable for natural mating due to the concentration of sperm from good to very good and their morphology. In addition, 68.33% presented a sperm concentration higher than the standard, it was established that the bulls are being used for mating at a ratio of 5%, without taking into account the service capacity. Therefore, it is important to apply andrological examination as a predictor of the bull/cow relationship in natural mating and to rule out bulls with subfertility problems, thus improving the reproductive efficiency of the stallion, having a great socioeconomic impact on the livestock sector of the region. Ecuadorian coastal region.